2011
DOI: 10.1039/c1dt10183h
|View full text |Cite
|
Sign up to set email alerts
|

Multimetal Fischer carbene complexes of Group VI transition metals: synthesis, structure and substituent effect investigation

Abstract: Fischer carbene complexes of tungsten with substituents containing up to two additional different transition metals, with all the metals in electronic contact with the carbene carbon atom, were synthesised and studied both in solution and in the solid state. For the complexes of the type [W(CO) 5 {C(OR¢)R}], the substituents chosen were heteroaromatic 2-benzo[b]thienyl (2-BT), or 2-BT p-bonded to a chromium tricarbonyl fragment ([Cr(CO) 3 (2-h 6 -BT)]) or ferrocenyl (Fc) as the R-substituent, while the OR¢-sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 54 publications
(24 reference statements)
1
22
1
Order By: Relevance
“…In all cases, only one reduction and only one oxidation were observed (so that both metal atoms participate in one molecular orbital) although there are two redox active metal atoms in the molecule [139]. This was in direct contrast to the recent electrochemical results obtained where heterodimetallic carbene complexes with a π-aryl metal carbene substituent showed that the two metal moieties in each complex function as separate, localized redox centres [140]. This implies that a direct comparison of substituent effects on the pentacarbonyl metal can be made.…”
Section: Complexes With a Metal Fragment Bonded To The Carbene Substicontrasting
confidence: 54%
See 2 more Smart Citations
“…In all cases, only one reduction and only one oxidation were observed (so that both metal atoms participate in one molecular orbital) although there are two redox active metal atoms in the molecule [139]. This was in direct contrast to the recent electrochemical results obtained where heterodimetallic carbene complexes with a π-aryl metal carbene substituent showed that the two metal moieties in each complex function as separate, localized redox centres [140]. This implies that a direct comparison of substituent effects on the pentacarbonyl metal can be made.…”
Section: Complexes With a Metal Fragment Bonded To The Carbene Substicontrasting
confidence: 54%
“…Structure data suggest a higher contribution of the acyl resonance structure in Fig. 43 to the bonding than in the alkoxycarbene complexes, with shorter M´-O bond lengths [140,151,159,170,186,187].…”
Section: Metaloxycarbene Complexesmentioning
confidence: 98%
See 1 more Smart Citation
“…3.34 μA), and since the ferrocenyl couple represents a one-electron transfer process, wave I must also represent a one-electron reduction process to initially generate − Cr-C˙, not only in 1, but also in the other carbene complexes of this study. This assignment is possible because it is known that the LUMO is mainly carbene-ligand based, 17 and single electron transfer reactions followed by ESI-MS have also indicated the formation of such − Cr-C˙species. 36 Since the orbitals associated with carbenes are delocalized over metal, carbon, and heteroatom, one can envisage the − Cr-C˙species as being stabilised by distributing charge and radical all over the ligand system.…”
Section: Electrochemistry and Molecular Orbital Analysesmentioning
confidence: 99%
“…[13] Fine-tuning of the steric and electronic properties of the carbene moiety can be effected by modulation of the carbene substituents (X = heteroatom substituent, R = aryl substituent). [14] The introduction of a metal-containing substituent, such as ferrocenyl, opens the door for the design of organometallic multi-tag complexes. To this end, mono-and biscarbene ferrocenyl complexes were also synthesized.…”
Section: Introductionmentioning
confidence: 99%